Teaching in extended programmes in South Africa by Lynn Coleman - Molefi Motsoenyane (University of Johannesburg, 2020)
In this review of Lynn Coleman's Teaching In Extended Programmes In South Africa, Molefi Motsoenyane explains how the book ably acts as a point of reference for teaching diverse students in a range of subjects, while also considering various administrative issues relating to extended curriculum provision. Key words: extended curriculum programmes, undergraduate students, teaching and learning, active learning, diversity How to cite this article: Motsoenyane, M. 2020. Book review: Coleman, L. 2018. Teaching In Extended Programmes In South Africa. Cape Town, South Africa: Fundani, Centre for Higher Education Development, Cape Peninsula University of Technology. Scholarship of Teaching and Learning in the South. v. 4, n. 1, p. 86-88. April 2020. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=144 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/